Nearly constant loss in crystalline oxide-ion conductor Gd2Zr2O7 - Diaz Guillen, M. R. (2014)
We present a study of the nearly constant loss regime in the oxide-ion conductor Gd2Zr2O7 by using Impedance Spectroscopy measurements. At enough low temperature, between 173 and 253 K, the dielectric loss is found to be almost temperature and frequency independent within the whole experimental frequency range (10 Hz – 1 MHz). However, a symmetric and very broad relaxation peak is clearly resolved in the loss spectra. This peak shows a thermally activated peak frequency with activation energy Eτ = 0.29 ± 0.02 eV, and its origin is discussed in terms of previously proposed models for the nearly constant loss.